Effect of Student’s Involvement in Fees Policy Implementation on Learner’s Stability in Public Universities in Uganda: The Case of Makerere University. - Oketch, Chrisostom; Tazwaire, Doreen (Kabale University, 2023)
The study examined the eff ect of student involvement/participation in fees policy implementation on learner’s stability in Makerere University that has had a number of student unrests in the past whenever fees policy changes are considered for implementation resulting into a number of disruptive consequences. The study aimed at examining how student involvement/ participation in fees policy implementation affect their stability with a view of proposing strategies capable of enhancing order in the university. The study adopted a case study design in collection and analysis of data using questionnaires and interview guide from a sample of 368 consisting of students, their leaders and selected university administrators. Results indicated that there is a gap on the part of student leaders to consult extensively from their constituents because they lack advocacy and lobbying skills, management rarely put into consideration student’s views while making decisions, and that protests are seen by students as a mobilization structure for airing out their voices on fees policy changes. The study concludes that the level of student involvement in fees policy implementation depends on the nature of student leadership and willingness of management to incorporate their views in decision making. The study recommends that individual student awareness and empowerment to participate in fees policy implementation is important and must be cultivated by university management and the need for capacity building on the part of student leaders to boost their representation skills. Key words: Educational Policy Implementation, Higher Education costs - Sub-Saharan Africa.